An analysis the financial performance in terms of Liquidity of Public Sector Bank Private Sector Bank to the credit and Deposit Ratio (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The investigation is crucial for the Indian economy. Due to the ever-changing nature of the Indian banking sector, it is first necessary to assess and compare the financial metrics of the nation's public and private banks. The proposed research makes several important advances to the study of banking and finance by comparing the performance measures of private and public banks in India. The study uses a sample size of two, with one bank representing the public sector (Indian Bank) and one representing the private sector (HDFC Bank). Two banks, one each from the public and private sectors, were chosen as a sample based on the size of the institutions' foundations. Primary data was collected through in-depth interviews, while secondary data was culled from select public and private sector banks' 2013-2022 annual reports.